2013
DOI: 10.1007/s00269-013-0584-6
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of Zn2SiO4 III and IV synthesized at 6.5–8 GPa and 1,273 K

Abstract: We report the crystal structures determined under ambient condition for two Zn 2 SiO 4 polymorphs synthesized at 6.5 GPa and 1,273 K (phase III) and 8 GPa and 1,273 K (phase IV) and also compare their 29 Si MAS NMR spectroscopic characteristics with those of other Zn 2 SiO 4 polymorphs (phases I, II and V). Electron microprobe analysis revealed that both of phases III and IV are stoichiometric like the lower-pressure polymorphs (phases I and II), contrary to previous report. The crystal structures were solved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…Partial occupancy of octahedral sites by Si is expected if Zn/Si disorder occurs. Previously reported 29 Si MAS NMR results with the same sample revealed no clear octahedral Si peak other than a minor coexisting ZnSiO 3 ilmenite phase (Liu et al, 2013), supporting the Rietveld result. However, a small degree of disorder cannot be ruled out for this system.…”
Section: A D V a N C E P U B L I C A T I O N A R T I C L Esupporting
confidence: 73%
See 4 more Smart Citations
“…Partial occupancy of octahedral sites by Si is expected if Zn/Si disorder occurs. Previously reported 29 Si MAS NMR results with the same sample revealed no clear octahedral Si peak other than a minor coexisting ZnSiO 3 ilmenite phase (Liu et al, 2013), supporting the Rietveld result. However, a small degree of disorder cannot be ruled out for this system.…”
Section: A D V a N C E P U B L I C A T I O N A R T I C L Esupporting
confidence: 73%
“…The cubic spinel phase was synthesized at 3 GPa and 1600°C for 1 h, whereas the tetragonal spinel phase was synthesized at 5 GPa and 1200°C for 1.7 h, following the studies of Ringwood and Major (1967) and Syono et al (1971). The modified spinel phase of Zn 2 SiO 4 used for this study is identical to that reported in our previous study using 29 Si MAS NMR spectroscopy (Liu et al, 2013). This sample was synthesized at 15 GPa and 1200°C for 1 h using the same press.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations